Distribution of genital wart human papillomavirus genotypes in China: A multi‐center study. Issue 10 (16th July 2013) - Chang, Lihong; Ci, Puwa; Shi, Jufang; Zhai, Kan; Feng, Xiaoli; Colombara, Danny; Wang, Wei; Qiao, Youlin; Chen, Wen; Wu, Yuping
Abstract Although it is understood that low‐risk human papillomavirus (HPV) genotypes are associated with genital warts, there have been very few published studies reporting the genotype‐specific prevalence of HPV among Chinese population. The aim of the study was to assess the prevalence of HPV genotypes in genital warts across China, and thus to evaluate the potential benefit of a quadrivalent HPV vaccine in this population. The tissue samples of a total of 1, 005 genital warts cases were collected from seven geographical regions of China. HPV genotypes were analyzed using the general primer PCR and sequence‐based typing method. Prevalence differences between sexes, geographical regions and age groups were assessed. The overall prevalence of HPV DNA in genital warts patients was 88.7% (891/1, 005). Low‐risk genotypes predominated, with a prevalence of 78.1% (785/1, 005). The most prevalent genotypes were HPV‐6 (41.3%), HPV‐11 (37.6%) and HPV‐16 (10.4%). Among HPV positive patients, single infections were more frequent (866/891, 97.2%) than co‐infections (25/891, 2.8%). Both the overall prevalence of HPV DNA and that of HPV‐6/‐11/‐16 (positive for any of the three types) decreased with age (P‐trend = 0.010 and P‐trend = 0.025, respectively). The prevalence of HPV‐6/‐11 (positive for either HPV type) and HPV‐16 varied by geographic region (P = 0.003 and P ≤ 0.001, respectively). The prevalence of HPV‐16 in female patients between urban and rural areas showed a marginally significant difference (P = 0.05). In sum, the results provide strong evidence that, in China, the most prevalent HPV genotypes in genital warts are HPV‐6, HPV‐11 and HPV‐16. This indicates that a quadrivalent HPV vaccine may decrease the incidence of genital warts in the future. J Med. Virol. 85:1765–1774, 2013. © 2013 Wiley Periodicals, Inc.